THE EFFECT OF THE COMBINATION OF SLOW STROKE BACK MASSAGE AND WILLIAM FLEXION EXERCISE IN OVERCOMING LOW BACK PAIN IN OPERATING ROOM NURSES AT KARUNIA KASIH JATIWARINGIN HOSPITAL IN 2023 - Hermawan, Iwan; Fauzi, Achmad (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: Low back pain (LBP) is pain that occurs in the lower back area and is caused by stress or strain on the muscles, tendons, and ligaments of the back that often occurs due to excessive activity. This pain can lead to an inability to perform normal activities (Yulianto et al., 2023). Research Objective: The general objective of this study is to determine the effect of combination therapy of slow stroke back massage and William flexion exercise on low back pain in operating room nurses. Research Methodology: The methodology used in this study uses The type of research used is quantitative descriptive research, which is a research process that uses a lot of numbers in its implementation starting from data collection, and interpretation to drawing conclusions Results Research: The results of the study found a significant relationship between the Effect of the Combination of Slow Stroke Back Massage and William Flexion Exercise in Overcoming Low Back Pain in Operating Room Nurses at Karunia Kasih Hospital Bekasi obtained p-value 0.000 Conclusions and suggestions: conclusions and suggestions from all these research activities can be concluded that there is a relationship between the Effect of the Combination of Slow Stroke Back Massage and William Flexion Exercise in Overcoming Low Back Pain in Operating Room Nurses at Karunia Kasih Hospital Bekasi. Therefore, it is expected that health efforts need to be maximally improved.